Resin composition and high frequency device

A resin composition with specific inorganic fillers and particle size distributions addresses the need for high fluidity and dielectric constant in antenna-in-package applications, enhancing the performance of high-frequency devices.

JP7613077B2Active Publication Date: 2025-01-15RESONAC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020206091
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-11
Publication Date
2025-01-15
Estimated Expiration
2040-12-11

AI Technical Summary

Technical Problem

The challenge lies in developing a resin composition that can provide excellent fluidity and a high dielectric constant for sealing materials in antenna-in-package (AiP) applications, which are becoming smaller and more sophisticated, while also supporting high-frequency operations.

Method used

A resin composition comprising an epoxy resin, a curing agent, a first inorganic filler containing a titanium element, and a second inorganic filler with a distinct particle size distribution, including multiple peak particle sizes, is used to create a cured product with enhanced fluidity and high dielectric constant.

Benefits of technology

The composition achieves a cured product with improved fluidity and high dielectric constant, suitable for high-frequency devices, particularly in antenna-in-package applications, by leveraging the properties of inorganic fillers with varied particle sizes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613077000001
    Figure 0007613077000001
Patent Text Reader

Abstract

To provide a resin composition that has excellent flowability and can give a cured product having a high relative dielectric constant, and a high-frequency device having a cured product of the resin composition.SOLUTION: A resin composition contains an epoxy resin, a curing agent, a first inorganic filler containing titanium element, and a second inorganic filler having a peak particle size of particle size distribution different from a peak particle size of particle size distribution of the first inorganic filler. The resin composition is used for molding a high-frequency device having an antenna.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a high-frequency device. [Background technology]

[0002] In recent years, with the demand for electronic devices to have higher functionality and to be lighter, thinner, shorter, and smaller, the integration and mounting of electronic components has become more and more dense, and the semiconductor packages used in these electronic devices are becoming smaller and smaller than ever before.Furthermore, the radio waves used for communication in electronic devices are becoming higher in frequency.

[0003] 2. Description of the Related Art From the viewpoints of miniaturization of semiconductor packages and compatibility with high frequencies, high dielectric constant epoxy resin compositions for use in sealing semiconductor elements have been proposed (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-36410 A Summary of the Invention [Problem to be solved by the invention]

[0005] Meanwhile, with the miniaturization and high performance of semiconductor packages (PKG), the development of antenna-in-package (AiP), which is a PKG with an antenna function, is also underway. By using a material with a high relative dielectric constant as the sealing material for sealing the antenna, it is possible to miniaturize the AiP.

[0006] Moreover, it is desirable for the resin composition, such as the sealing material for sealing the antenna, to have high fluidity from the viewpoint of moldability.

[0007] An object of the present disclosure is to provide a resin composition that is capable of producing a cured product having excellent fluidity and a high dielectric constant, and a high-frequency device having a cured product obtained by curing the resin composition. [Means for solving the problem]

[0008] Specific means for solving the above problems include the following aspects. <1> A resin composition for use in molding a high-frequency device having an antenna, comprising: an epoxy resin; a curing agent; a first inorganic filler containing elemental titanium; and a second inorganic filler having a peak particle size in a particle size distribution different from the peak particle size in the particle size distribution of the first inorganic filler. <2> The first inorganic filler has a relative dielectric constant of 10 or more at 10 GHz. <1> The resin composition according to claim 1. <3> The content of the first inorganic filler is 60% by mass to 95% by mass based on the total amount of the first inorganic filler and the second inorganic filler. <1> or <2> The resin composition according to claim 1. <4> The particle size distribution of the combination of the first inorganic filler and the second inorganic filler has at least three peaks. <1> ~ <3> 10. The resin composition according to claim 9 . <5> The second inorganic filler includes a third inorganic filler having a peak particle size of 0.1 μm to 5 μm in particle size distribution, and a fourth inorganic filler having a peak particle size of 7 μm to 100 μm in particle size distribution. <1> ~ <4> 10. The resin composition according to claim 9 . <6> The first inorganic filler has a peak particle size in a particle size distribution that is larger than the peak particle size of the third inorganic filler and smaller than the peak particle size of the fourth inorganic filler. <5> The resin composition according to claim 1. <7> The mass ratio of the fourth inorganic filler to the third inorganic filler (fourth inorganic filler / third inorganic filler) is 0.1 to 5. <5> or <6> The resin composition according to claim 1. <8> The second inorganic filler contains at least one of alumina and silica. <1> ~ <7> 10. The resin composition according to claim 9 . <9> The first inorganic filler contains at least one selected from the group consisting of barium titanate, calcium titanate, and strontium titanate. <1> ~ <8> 10. The resin composition according to claim 9 . <10> A resin composition comprising an epoxy resin, a curing agent, and an inorganic filler, the particle size distribution of the inorganic filler having at least three peaks, the inorganic filler comprising a first inorganic filler containing elemental titanium. <11> The particle size distribution of the inorganic filler has a first peak located in the range of 0.1 μm to 5 μm, a second peak located in the range of 0.5 μm to 30 μm, and a third peak located in the range of 7 μm to 100 μm, and the value of the first peak<the value of the second peak<the value of the third peak. <10> The resin composition according to claim 1. <12> The antenna, <1> ~ <11> and a cured product of the resin composition according to any one of the above items. Effect of the Invention

[0009] According to the present disclosure, it is possible to provide a resin composition that can produce a cured product having excellent fluidity and a high dielectric constant, and a high-frequency device having a cured product obtained by curing this resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In the present disclosure, the term "step" includes not only a step that is independent of other steps, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved. In the present disclosure, a numerical range indicated using "~" includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In the present disclosure, each component may contain multiple types of the corresponding substance. When multiple substances corresponding to each component are present in the composition, the content or amount of each component means the total content or amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, the particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.

[0011] <Resin composition> The resin composition of the present disclosure contains an epoxy resin, a curing agent, a first inorganic filler containing elemental titanium, and a second inorganic filler having a peak particle size in a particle size distribution different from the peak particle size in the particle size distribution of the first inorganic filler, and is a resin composition for use in molding a high-frequency device having an antenna.

[0012] The resin composition of the present disclosure contains a first inorganic filler and a second inorganic filler, and therefore it is possible to produce a cured product having excellent fluidity and a high relative dielectric constant. The reason for this is presumed to be as follows. The resin composition of the present disclosure contains a first inorganic filler containing titanium element, and therefore it is possible to produce a cured product having a high relative dielectric constant. Furthermore, the resin composition of the present disclosure contains two or more inorganic fillers with different peak particle sizes, and therefore it has excellent fluidity.

[0013] The resin composition of the present disclosure is not limited to a configuration containing two kinds of inorganic fillers with different peak particle sizes. For example, the first inorganic filler containing titanium element may be composed of two or more inorganic fillers containing titanium element and having different peak particle sizes, and the second inorganic filler may be composed of two or more inorganic fillers with different peak particle sizes. When the first inorganic filler contains titanium element and is composed of two or more inorganic fillers with different peak particle sizes, the second inorganic filler may have a peak particle size different from any one of the two or more inorganic fillers with different peak particle sizes in the first inorganic filler. When the second inorganic filler is composed of two or more inorganic fillers with different peak particle sizes, the first inorganic filler may have a peak particle size different from any one of the two or more inorganic fillers with different peak particle sizes in the second inorganic filler.

[0014] The resin composition of the present disclosure is a resin composition for use in molding in a high-frequency device having an antenna, and is used to manufacture a resin molded product using various molding methods such as low-pressure transfer molding, injection molding, and compression molding. The resin composition of the present disclosure may be a composition used to seal an antenna. The resin composition is preferably used for semiconductor packaging applications that require both a high relative dielectric constant and a low dielectric loss tangent, and is more preferably used, for example, in an antenna-in-package (AIP).

[0015] Each component constituting the resin composition will be described below. The resin composition of the present embodiment contains an epoxy resin, a curing agent, a first inorganic filler, and a second inorganic filler, and may contain other components as necessary.

[0016] (Epoxy resin) The type of epoxy resin is not particularly limited as long as it has an epoxy group in the molecule.

[0017] Specific examples of epoxy resins include novolac-type epoxy resins (phenol novolac-type epoxy resins, orthocresol novolac-type epoxy resins, etc.) obtained by epoxidizing novolac resins obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenolic compounds such as phenol, cresol, xylenol, resorcin, catechol, bisphenol A, bisphenol F, etc., and naphthol compounds such as α-naphthol, β-naphthol, dihydroxynaphthalene, etc., with an aliphatic aldehyde compound such as formaldehyde, acetaldehyde, propionaldehyde, etc., under an acidic catalyst; triphenylmethane-type epoxy resins obtained by epoxidizing triphenylmethane-type phenolic resins obtained by condensing or co-condensing the above-mentioned phenolic compound with an aromatic aldehyde compound such as benzaldehyde, salicylaldehyde, etc., under an acidic catalyst; and novolac resins obtained by co-condensing the above-mentioned phenolic compound and naphthol compound with an aldehyde compound under an acidic catalyst. diphenylmethane type epoxy resins which are diglycidyl ethers of bisphenol A, bisphenol F, etc.; biphenyl type epoxy resins which are diglycidyl ethers of alkyl-substituted or unsubstituted biphenols; stilbene type epoxy resins which are diglycidyl ethers of stilbene-based phenolic compounds; sulfur-containing epoxy resins which are diglycidyl ethers of bisphenol S, etc.; epoxy resins which are glycidyl ethers of alcohols such as butanediol, polyethylene glycol, and polypropylene glycol; glycidyl ester type epoxy resins which are glycidyl esters of polyvalent carboxylic acid compounds such as phthalic acid, isophthalic acid, and tetrahydrophthalic acid; glycidylamine type epoxy resins in which active hydrogen bonded to nitrogen atoms of aniline, diaminodiphenylmethane, isocyanuric acid, etc. is substituted with a glycidyl group; dicyclopentadiene type epoxy resins which are epoxidized co-condensation resins of dicyclopentadiene and phenolic compounds;Alicyclic epoxy resins such as vinylcyclohexene diepoxide, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and 2-(3,4-epoxy)cyclohexyl-5,5-spiro(3,4-epoxy)cyclohexane-m-dioxane, which are epoxy-modified epoxy resins in which the olefin bonds in the molecule have been epoxidized; paraxylylene-modified epoxy resins, which are glycidyl ethers of paraxylylene-modified phenolic resins; metaxylylene-modified epoxy resins, which are glycidyl ethers of metaxylylene-modified phenolic resins; terpene-modified epoxy resins, which are glycidyl ethers of terpene-modified phenolic resins; and dicyclopentadiene-modified phenolic resins, which are glycidyl ethers of dicyclopentadiene-modified phenolic resins. Examples of the epoxy resin include pentadiene-modified epoxy resins; cyclopentadiene-modified epoxy resins which are glycidyl ethers of cyclopentadiene-modified phenolic resins; polycyclic aromatic ring-modified epoxy resins which are glycidyl ethers of polycyclic aromatic ring-modified phenolic resins; naphthalene-type epoxy resins which are glycidyl ethers of naphthalene ring-containing phenolic resins; halogenated phenol novolac-type epoxy resins; hydroquinone-type epoxy resins; trimethylolpropane-type epoxy resins; linear aliphatic epoxy resins obtained by oxidizing olefin bonds with peracids such as peracetic acid; aralkyl-type epoxy resins obtained by epoxidizing aralkyl-type phenolic resins such as phenol aralkyl resins and naphthol aralkyl resins; and the like. Furthermore, epoxy-oxidized acrylic resins and the like can also be mentioned as epoxy resins. These epoxy resins may be used alone or in combination of two or more.; From the viewpoint of heat resistance, the epoxy resin preferably contains a triphenylmethane type epoxy resin.

[0018] The epoxy equivalent (molecular weight / number of epoxy groups) of the epoxy resin is not particularly limited, but from the viewpoint of the balance of various properties such as moldability, heat resistance, and electrical reliability, it is preferably 100 g / eq to 1000 g / eq, and more preferably 150 g / eq to 500 g / eq.

[0019] The epoxy equivalent of the epoxy resin is a value measured by a method conforming to JIS K 7236:2009.

[0020] When the epoxy resin is solid, its softening point or melting point is not particularly limited, but is preferably 40°C to 180°C from the viewpoints of moldability and heat resistance, and more preferably 50°C to 130°C from the viewpoint of handleability during preparation of the resin composition.

[0021] The softening point or melting point of the epoxy resin is a value measured by differential scanning calorimetry (DSC) or a method in accordance with JIS K 7234:1986 (ring and ball method).

[0022] From the viewpoints of strength, fluidity, heat resistance, moldability, etc., the content of the epoxy resin in the resin composition is preferably 0.5% by mass to 20% by mass, more preferably 2% by mass to 15% by mass, and even more preferably 3% by mass to 10% by mass.

[0023] (hardening agent) The resin composition contains a curing agent. The curing agent may be any compound having a functional group that reacts with the epoxy group in the epoxy resin.

[0024] The curing agent is not particularly limited, and examples thereof include phenol curing agents, amine curing agents, acid anhydride curing agents, polymercaptan curing agents, polyaminoamide curing agents, isocyanate curing agents, blocked isocyanate curing agents, ester curing agents, etc. These curing agents may be used alone or in combination of two or more.

[0025] From the viewpoint of keeping the dielectric tangent of the cured product low and from the viewpoint of moldability, the curing agent may contain a phenol curing agent.

[0026] Specific examples of the phenolic hardener include polyhydric phenolic compounds such as resorcin, catechol, bisphenol A, bisphenol F, and substituted or unsubstituted biphenol; novolak-type phenolic resins obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenolic compounds such as phenol, cresol, xylenol, resorcin, catechol, bisphenol A, bisphenol F, phenylphenol, and aminophenol, and naphthol compounds such as α-naphthol, β-naphthol, and dihydroxynaphthalene, with an aldehyde compound such as formaldehyde, acetaldehyde, or propionaldehyde, under an acidic catalyst; and polyphenolic compounds synthesized from the above phenolic compounds and dimethoxyparaxylene, bis(methoxymethyl)biphenyl, or the like. Examples of the phenol curing agent include aralkyl-type phenolic resins such as phenol aralkyl resins and naphthol aralkyl resins; paraxylylene-modified phenolic resins, metaxylylene-modified phenolic resins; melamine-modified phenolic resins; terpene-modified phenolic resins; dicyclopentadiene-type phenolic resins and dicyclopentadiene-type naphthol resins synthesized by copolymerization of the above-mentioned phenolic compounds and dicyclopentadiene; cyclopentadiene-modified phenolic resins; polycyclic aromatic ring-modified phenolic resins; biphenyl-type phenolic resins; triphenylmethane-type phenolic resins obtained by condensing or co-condensing the above-mentioned phenolic compounds with aromatic aldehyde compounds such as benzaldehyde and salicylaldehyde under an acid catalyst; and phenolic resins obtained by copolymerizing two or more of these. These phenolic curing agents may be used alone or in combination of two or more.

[0027] The functional group equivalent of the curing agent (for example, the hydroxyl group equivalent in the case of a phenolic curing agent) is not particularly limited. From the viewpoint of the balance of various properties such as moldability, heat resistance, and electrical reliability, it is preferably 70 g / eq to 1000 g / eq, and more preferably 80 g / eq to 500 g / eq. The functional group equivalent of the curing agent (for example, the hydroxyl group equivalent in the case of a phenolic curing agent) is a value measured by a method in accordance with JIS K 0070:1992.

[0028] When the curing agent is a solid, its softening point or melting point is not particularly limited. From the viewpoints of moldability and heat resistance, it is preferably 40° C. to 180° C., and from the viewpoint of handleability during production of the resin composition, it is more preferably 50° C. to 130° C.

[0029] The softening point or melting point of the curing agent is a value measured in the same manner as the softening point or melting point of the epoxy resin.

[0030] The equivalent ratio of the epoxy resin to the curing agent, that is, the ratio of the number of functional groups in the curing agent to the number of functional groups in the epoxy resin (number of functional groups in the curing agent / number of functional groups in the epoxy resin) is not particularly limited. From the viewpoint of keeping the amount of unreacted components low, it is preferably set in the range of 0.5 to 2.0, and more preferably set in the range of 0.6 to 1.3. From the viewpoint of moldability and heat resistance, it is further preferably set in the range of 0.8 to 1.2.

[0031] (Cure accelerator) The resin composition may contain a curing accelerator. The type of the curing accelerator is not particularly limited and can be selected depending on the type of epoxy resin or curing agent, the desired properties of the resin composition, and the like.

[0032] Examples of the curing accelerator include diazabicycloalkenes such as 1,5-diazabicyclo[4.3.0]nonene-5 (DBN) and 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), cyclic amidine compounds such as 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, and 2-heptadecylimidazole; derivatives of the cyclic amidine compounds; phenol novolac salts of the cyclic amidine compounds or their derivatives; Compounds with intramolecular polarization obtained by adding compounds with π bonds such as quinone compounds such as maleic anhydride, 1,4-benzoquinone, 2,5-toluquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, and phenyl-1,4-benzoquinone, and diazophenylmethane to these compounds; cyclic amidinium compounds and compounds obtained by adding isocyanates, such as tetraphenylborate salts of DBN, tetraphenylborate salts of 2-ethyl-4-methylimidazole, and tetraphenylborate salts of N-methylmorpholine; isocyanate adducts of DBU, isocyanate adducts of DBN, isocyanate adducts of 2-ethyl-4-methylimidazole, and isocyanate adducts of N-methylmorpholine; tertiary amine compounds, such as pyridine, triethylamine, triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol; derivatives of the above tertiary amine compounds; ammonium salt compounds, such as tetra-n-butylammonium acetate, tetra-n-butylammonium phosphate, tetraethylammonium acetate, tetra-n-hexylammonium benzoate, and tetrapropylammonium hydroxide;organic phosphines such as primary phosphines, e.g., ethylphosphine, phenylphosphine, etc.; secondary phosphines, e.g., dimethylphosphine, diphenylphosphine, etc.; and tertiary phosphines, e.g., triphenylphosphine, diphenyl(p-tolyl)phosphine, tris(alkylphenyl)phosphine, tris(alkoxyphenyl)phosphine, tris(alkyl alkoxyphenyl)phosphine, tris(dialkylphenyl)phosphine, tris(trialkylphenyl)phosphine, tris(tetraalkylphenyl)phosphine, tris(dialkoxyphenyl)phosphine, tris(trialkoxyphenyl)phosphine, tris(tetraalkoxyphenyl)phosphine, trialkylphosphine, dialkylarylphosphine, alkyldiarylphosphine, trinaphthylphosphine, tris(benzyl)phosphine, etc.; phosphine compounds, e.g., complexes of the organic phosphines and organic borons; and complexes of the organic phosphines or the phosphine compounds with maleic anhydride, 1,4-benzoquinone, 2,5-toluquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone , 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, phenyl-1,4-benzoquinone, anthraquinone, or other quinone compounds, or diazophenylmethane or other compounds having a π bond, and having intramolecular polarization; A compound having intramolecular polarization, obtained by reacting a halogenated phenol compound such as 3-iodophenol, 2-iodophenol, 4-bromo-2-methylphenol, 4-bromo-3-methylphenol, 4-bromo-2,6-dimethylphenol, 4-bromo-3,5-dimethylphenol, 4-bromo-2,6-di-tert-butylphenol, 4-chloro-1-naphthol, 1-bromo-2-naphthol, 6-bromo-2-naphthol, or 4-bromo-4'-hydroxybiphenyl, followed by a dehydrohalogenation process;Examples of the tetra-substituted phosphonium include tetra-substituted phosphonium compounds such as tetraphenylphosphonium, tetraphenylborate salts of tetra-substituted phosphonium such as tetraphenylphosphonium tetra-p-tolylborate, and salts of tetra-substituted phosphonium with phenolic compounds; salts of tetraalkylphosphonium with partial hydrolysates of aromatic carboxylic acid anhydrides; phosphobetaine compounds; and adducts of phosphonium compounds with silane compounds. The curing accelerators may be used alone or in combination of two or more. Among these, particularly suitable curing accelerators include triphenylphosphine, an adduct of triphenylphosphine and a quinone compound, an adduct of tributylphosphine and a quinone compound, and an adduct of tri-p-tolylphosphine and a quinone compound.

[0033] When the resin composition contains a curing accelerator, the amount is preferably 0.1 to 30 parts by mass, more preferably 1 to 15 parts by mass, per 100 parts by mass of the resin component (total amount of the epoxy resin and the curing agent). When the amount of the curing accelerator is 0.1 parts by mass or more per 100 parts by mass of the resin component, the composition tends to cure well in a short time. When the amount of the curing accelerator is 30 parts by mass or less per 100 parts by mass of the resin component, the curing speed is not too fast and a good molded product tends to be obtained.

[0034] (First inorganic filler) The resin composition contains a first inorganic filler containing elemental titanium. The first inorganic filler may be used alone or in combination of two or more kinds.

[0035] The first inorganic filler preferably has a relative dielectric constant of 10 or more, more preferably 10-100, and further preferably 30-100 at 10 GHz.

[0036] In the present disclosure, the relative dielectric constant at 10 GHz in the inorganic filler is a value obtained as follows. First, a resin composition consisting of 100 parts by mass of epoxy resin (biphenyl aralkyl type epoxy resin, epoxy equivalent 274 g / eq), 74.8 parts by mass of phenol curing agent (phenol aralkyl resin, hydroxyl equivalent 205 g / eq), and 2 parts by mass of 1,4-benzoquinone adduct of triphenylphosphine, an inorganic filler, and methyl ethyl ketone (MEK) are mixed, and the aforementioned resin composition is dissolved in MEK to prepare a varnish containing 75 mass% of the resin composition and the inorganic filler in total. At this time, varnishes containing 10 volume %, 20 volume %, and 30 volume % of the inorganic filler relative to the solid content excluding the solvent are prepared, respectively. The obtained varnish was applied onto a substrate, and the substrate was dried at 100°C for 10 minutes, after which the resin film was peeled off from the substrate. The obtained resin film was molded by compression molding under conditions of a mold temperature of 175°C, molding pressure of 6.9MPa, and curing time of 600 seconds to obtain a cured product for measurement. The relative dielectric constant at 10GHz of each of the obtained cured products for measurement was measured, and a graph was created in which the content of the inorganic filler was plotted on the horizontal axis and the measured value of the relative dielectric constant was plotted on the vertical axis. From the obtained graph, a linear approximation was performed by the least squares method, and the relative dielectric constant when the content of the inorganic filler was 100% by volume was obtained by extrapolation, and this was taken as the "relative dielectric constant of the entire inorganic filler".

[0037] From the viewpoint of obtaining a cured product having a high relative dielectric constant, the first inorganic filler preferably contains at least one selected from the group consisting of barium titanate, calcium titanate, strontium titanate, zinc zirconate titanate, and titanium oxide, and more preferably contains at least one selected from the group consisting of barium titanate, calcium titanate, and strontium titanate. Among them, from the viewpoint of high sphericity and high fluidity, it is preferable to contain barium titanate.

[0038] In the first inorganic filler, the peak particle size in the particle size distribution is preferably 0.1 μm to 100 μm, more preferably 0.5 μm to 30 μm, further preferably 2 μm to 15 μm, and particularly preferably 3 μm to 10 μm.

[0039] In the present disclosure, the peak particle size of the inorganic filler can be measured as follows. The resin composition is placed in a crucible and left at 800°C for 4 hours to be incinerated. The particle size distribution of the inorganic filler obtained by incineration is determined using an image particle size distribution analyzer equipped with a Raman spectrometer (e.g., Morphologi 4-ID by Malvern Panalytical Co., Ltd.), and the peak particle size of the inorganic filler can be determined from the particle size distribution.

[0040] From the viewpoint of fluidity of the resin composition, the first inorganic filler may be two or more types of inorganic fillers having different peak particle diameters in the particle size distribution, or may be two types of inorganic fillers having different peak particle diameters in the particle size distribution.

[0041] The shape of the first inorganic filler is not particularly limited, and examples thereof include a spherical shape, an elliptical shape, an irregular shape, etc. The first inorganic filler may be crushed.

[0042] The content of the first inorganic filler may be 60% by mass to 95% by mass, 70% by mass to 90% by mass, or 80% by mass to 90% by mass, based on the total amount of the first inorganic filler and the second inorganic filler. When the content of the first inorganic filler is 60% by mass or more, the relative dielectric constant tends to be higher when the resin composition is cured. When the content of the first inorganic filler is 95% by mass or less, the resin composition tends to have excellent flowability.

[0043] The content of the first inorganic filler may be 40% by volume to 95% by volume, 50% by volume to 90% by volume, or 65% by volume to 80% by volume, based on the total amount of the first inorganic filler and the second inorganic filler. When the content of the first inorganic filler is 40% by volume or more, the relative dielectric constant tends to be higher when the resin composition is cured. When the content of the first inorganic filler is 95% by volume or less, the resin composition tends to have excellent flowability.

[0044] (Second inorganic filler) The resin composition contains a second inorganic filler having a particle size distribution peak particle size different from that of the first inorganic filler. The second inorganic filler may be used alone or in combination of two or more.

[0045] The second inorganic filler may have a relative dielectric constant of less than 10, less than 8, or less than 5 at 10 GHz.

[0046] The type of the second inorganic filler is not particularly limited. Specific examples include inorganic materials such as fused silica, crystalline silica, glass, alumina, talc, clay, and mica. As the second inorganic filler, an inorganic filler having a flame retardant effect may be used. Examples of inorganic fillers having a flame retardant effect include aluminum hydroxide, magnesium hydroxide, composite metal hydroxides such as composite hydroxides of magnesium and zinc, and zinc borate. The second inorganic filler may or may not contain titanium element.

[0047] Among the second inorganic fillers, silica such as fused silica is preferred from the viewpoint of reducing the linear expansion coefficient, and alumina is preferred from the viewpoint of high thermal conductivity. The form of the second inorganic filler may be powder, beads obtained by sphering powder, fibers, etc.

[0048] The second inorganic filler preferably has a peak particle size in the particle size distribution of 0.1 μm to 100 μm, and more preferably 0.5 μm to 50 μm.

[0049] From the viewpoint of fluidity of the resin composition, the second inorganic filler may be two or more types of inorganic fillers having different peak particle diameters in the particle size distribution, or may be two types of inorganic fillers having different peak particle diameters in the particle size distribution.

[0050] In the resin composition of the present disclosure, from the viewpoint of the flowability of the resin composition, it is preferable that the particle size distribution of the combination of the first inorganic filler and the second inorganic filler has at least three peaks. In this case, it is sufficient that there is one or more peaks derived from the first inorganic filler and one or more peaks derived from the second inorganic filler.

[0051] The particle size distribution of the combination of the first inorganic filler and the second inorganic filler may be determined as follows: The particle size distribution of the first inorganic filler and the second inorganic filler may be determined using the image particle size distribution meter equipped with the above-mentioned Raman spectrometer, and the determined particle size distributions may be combined.

[0052] When the particle size distribution of the combination of the first inorganic filler and the second inorganic filler has three or more peaks, it is preferable that a first peak is located in the range of 0.1 μm to 5 μm, a second peak is located in the range of 0.5 μm to 30 μm, and a third peak is located in the range of 7 μm to 100 μm, and the value of the first peak<the value of the second peak<the value of the third peak.

[0053] The first peak is preferably located in the range of 0.1 μm to 3 μm, and more preferably in the range of 0.1 μm to 2 μm.

[0054] The second peak is preferably located in the range of 2 μm to 15 μm, and more preferably in the range of 3 μm to 10 μm.

[0055] The third peak is preferably located in the range of 7 μm to 80 μm, and more preferably in the range of 10 μm to 60 μm.

[0056] When the particle size distribution of the combination of the first inorganic filler and the second inorganic filler has three or more peaks, for example, there may be one or two or more peaks derived from the first inorganic filler and two or three or more peaks derived from the second inorganic filler.

[0057] From the viewpoint of fluidity of the resin composition, the second inorganic filler preferably includes a third inorganic filler having a peak particle size of 0.1 μm to 5 μm in the particle size distribution, and a fourth inorganic filler having a peak particle size of 7 μm to 100 μm in the particle size distribution.

[0058] In the first inorganic filler, the peak particle size of the particle size distribution is preferably larger than that of the third inorganic filler and smaller than that of the fourth inorganic filler. In this case, the first peak may be a peak derived from the third inorganic filler, the second peak may be a peak derived from the first inorganic filler, and the third peak may be a peak derived from the fourth inorganic filler.

[0059] The mass ratio of the fourth inorganic filler to the third inorganic filler (fourth inorganic filler / third inorganic filler) is preferably 0.1 to 5, more preferably 0.5 to 4, and even more preferably 1 to 3, from the viewpoint of the fluidity of the resin composition.

[0060] The total content of the first inorganic filler and the second inorganic filler is not particularly limited, and from the viewpoint of fluidity and strength, it is preferably 50% by mass to 95% by mass, more preferably 60% by mass to 95% by mass, and even more preferably 70% by mass to 90% by mass, based on the entire resin composition. When the total content of the first inorganic filler and the second inorganic filler is 50% by mass or more, the properties of the cured product, such as the relative dielectric constant, thermal expansion coefficient, thermal conductivity, and elastic modulus, tend to be further improved. When the total content of the first inorganic filler and the second inorganic filler is 95% by mass or less, the increase in viscosity of the resin composition is suppressed, the fluidity is further improved, and the moldability tends to be better.

[0061] In addition to the above-mentioned components, the resin composition may contain various additives such as coupling agents, ion exchangers, release agents, flame retardants, colorants, stress relaxation agents, etc. In addition to the additives exemplified below, the resin composition may contain various additives known in the art as necessary.

[0062] (Coupling Agent) The resin composition may contain a coupling agent. From the viewpoint of increasing the adhesion between the resin component and the inorganic filler, the resin composition preferably contains a coupling agent. Examples of the coupling agent include known coupling agents such as silane-based compounds such as epoxysilane, mercaptosilane, aminosilane, alkylsilane, ureidosilane, vinylsilane, and disilazane, titanium-based compounds, aluminum chelate compounds, and aluminum / zirconium-based compounds.

[0063] When the resin composition contains a coupling agent, the amount of the coupling agent is preferably 0.05 parts by mass to 5 parts by mass, more preferably 0.1 parts by mass to 2.5 parts by mass, relative to 100 parts by mass of the total of the first inorganic filler and the second inorganic filler. When the amount of the coupling agent is 0.05 parts by mass or more, the adhesion to the frame tends to be improved. When the amount of the coupling agent is 5 parts by mass or less, the moldability of the package tends to be improved.

[0064] (Ion exchanger) The resin composition may contain an ion exchanger. In order to improve the moisture resistance and high-temperature storage characteristics of a high-frequency device including a cured product of the resin composition, it is preferable to contain an ion exchanger. The ion exchanger is not particularly limited, and a conventionally known ion exchanger can be used. Specific examples include hydrotalcite compounds and hydrated oxides of at least one element selected from the group consisting of magnesium, aluminum, titanium, zirconium, and bismuth. The ion exchanger may be used alone or in combination of two or more. Among them, hydrotalcite represented by the following general formula (A) is preferable.

[0065] Mg (1-X) Al X (OH)2(CO3) X / 2 ·mH2O ……(A) (0 < X ≦ 0.5, m is a positive number)

[0066] When the resin composition contains an ion exchanger, its content is not particularly limited as long as it is sufficient to capture ions such as halogen ions. For example, it is preferably 0.1 part by mass to 30 parts by mass, more preferably 1 part by mass to 10 parts by mass, based on 100 parts by mass of the resin component (total amount of epoxy resin and curing agent).

[0067] (Release agent) The resin composition may contain a release agent from the viewpoint of obtaining good mold release properties with the mold during molding. The release agent is not particularly limited, and conventionally known ones can be used. Specifically, examples include higher fatty acids such as carnauba wax, montanic acid, and stearic acid, metal salts of higher fatty acids, ester waxes such as montanic acid esters, and polyolefin waxes such as oxidized polyethylene and non-oxidized polyethylene. The release agent may be used alone or in combination of two or more.

[0068] When the resin composition contains a release agent, its amount is preferably 0.01 part by mass to 10 parts by mass, more preferably 0.1 part by mass to 5 parts by mass, based on 100 parts by mass of the resin component (total amount of epoxy resin and curing agent). When the amount of the release agent is 0.01 part by mass or more based on 100 parts by mass of the resin component, mold release properties tend to be sufficiently obtained. When it is 10 parts by mass or less, better adhesion properties tend to be obtained.

[0069] (Flame retardant) The resin composition may contain a flame retardant. The flame retardant is not particularly limited, and conventionally known ones can be used. Specifically, examples include organic or inorganic compounds containing a halogen atom, antimony atom, nitrogen atom, or phosphorus atom, and metal hydroxides. The flame retardant may be used alone or in combination of two or more.

[0070] When the resin composition contains a flame retardant, the amount is not particularly limited as long as it is an amount sufficient to obtain the desired flame retardant effect. For example, the amount is preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, per 100 parts by mass of the resin component (total amount of the epoxy resin and the curing agent).

[0071] (Coloring agent) The resin composition may contain a colorant. Examples of the colorant include known colorants such as carbon black, organic dyes, organic pigments, titanium oxide, red lead, and red iron oxide. The content of the colorant can be appropriately selected depending on the purpose. The colorant may be used alone or in combination of two or more.

[0072] (Stress reliever) The resin composition may contain a stress relaxation agent. By containing a stress relaxation agent, it is possible to further reduce the warpage deformation of the package and the occurrence of package cracks. Examples of the stress relaxation agent include known stress relaxation agents (flexible agents) that are generally used. Specifically, examples include thermoplastic elastomers such as silicone-based, styrene-based, olefin-based, urethane-based, polyester-based, polyether-based, polyamide-based, and polybutadiene-based elastomers, rubber particles such as NR (natural rubber), NBR (acrylonitrile-butadiene rubber), acrylic rubber, urethane rubber, and silicone powder, and rubber particles having a core-shell structure such as methyl methacrylate-styrene-butadiene copolymer (MBS), methyl methacrylate-silicone copolymer, and methyl methacrylate-butyl acrylate copolymer. The stress relaxation agent may be used alone or in combination of two or more types.

[0073] Among the stress relaxation agents, silicone-based stress relaxation agents are preferred. Examples of silicone-based stress relaxation agents include those having an epoxy group, those having an amino group, and those modified with polyether, and silicone compounds such as silicone compounds having an epoxy group and polyether-based silicone compounds are more preferred. Among them, polyether-based silicone compounds are preferred from the viewpoint of reducing the dielectric loss tangent of the cured product and suppressing the appearance defects of the cured product.

[0074] The polyether silicone compound is not particularly limited as long as it is a compound in which a polyether group is introduced into silicone, which is a polymeric compound having a main skeleton formed by siloxane bonds. The polyether silicone compound may be used alone or in combination of two or more kinds. The polyether silicone compound may be a side-chain modified polyether silicone compound or a terminal modified polyether silicone compound. Among these, the polyether silicone compound is preferably a side-chain modified polyether silicone compound from the viewpoint of suppressing poor appearance of the cured product.

[0075] An example of the polyether silicone compound is an epoxy-polyether silicone compound. The epoxy-polyether silicone compound is not particularly limited as long as it is a compound in which a polyether group and an epoxy group are introduced into silicone, which is a polymeric compound having a main skeleton formed by siloxane bonds. The epoxy polyether silicone compound may be a side-chain modified epoxy polyether silicone compound, a terminal modified epoxy polyether silicone compound, or a side-chain and terminal modified epoxy polyether silicone compound. The main skeleton of the epoxy polyether silicone compound is preferably polydimethylsiloxane. The polyether group is preferably a polyether group in which one or both of ethylene oxide and propylene oxide are polymerized. The epoxy-polyether silicone compound is preferably a side-chain modified epoxy-polyether silicone compound in which a polyether group (preferably a polyether group obtained by polymerizing one or both of ethylene oxide and propylene oxide) and an epoxy group are each present in the side chain of silicone (preferably polydimethylsiloxane).

[0076] When the resin composition contains a stress relaxation agent, the amount thereof is, for example, preferably 1 to 30 parts by mass, and more preferably 2 to 20 parts by mass, per 100 parts by mass of the resin component (the total amount of the epoxy resin and the curing agent).

[0077] (Method for preparing resin composition) The method for preparing the resin composition is not particularly limited. A general method includes a method in which a predetermined amount of components is thoroughly mixed with a mixer or the like, then melt-kneaded with a mixing roll, an extruder, or the like, cooled, and pulverized. More specifically, for example, a method in which a predetermined amount of the above-mentioned components is uniformly stirred and mixed, kneaded with a kneader, roll, extruder, or the like that has been heated to 70°C to 140°C in advance, cooled, and pulverized can be mentioned.

[0078] The resin composition is preferably solid at room temperature and normal pressure (for example, 25°C, atmospheric pressure). When the resin composition is solid, the shape is not particularly limited, and examples thereof include powder, granules, tablets, etc. When the resin composition is in tablet form, the dimensions and mass are preferably set to be suitable for the molding conditions of the package from the viewpoint of handling.

[0079] <Modifications of Resin Composition> A modified example of the resin composition of the present disclosure will be described. The modified example of the resin composition of the present disclosure is a resin composition containing an epoxy resin, a curing agent, and an inorganic filler, the particle size distribution of the inorganic filler having at least three peaks, and the inorganic filler containing a first inorganic filler containing titanium element. The modified example of the resin composition may be appropriately combined with the forms described in the above-mentioned section on the resin composition of the present disclosure.

[0080] The modified resin composition of the present disclosure can produce a cured product having excellent fluidity and a high dielectric constant. The reason for this is presumably that the inclusion of the first inorganic filler containing titanium element allows the production of a cured product having a high dielectric constant, and the particle size distribution of the inorganic filler has at least three peaks, which gives the resin composition excellent fluidity.

[0081] In a modified version of the resin composition of the present disclosure, the first inorganic filler containing titanium element may be composed of three or more inorganic fillers containing titanium element and having different peak particle sizes. Alternatively, the modified version of the resin composition of the present disclosure may contain the second inorganic filler contained in the resin composition of the present disclosure described above, and the particle size distribution of the combination of the first inorganic filler and the second inorganic filler may have at least three peaks.

[0082] In a modified example of the resin composition of the present disclosure, it is preferable that the particle size distribution of the inorganic filler has a first peak located in the range of 0.1 μm to 5 μm, a second peak located in the range of 0.5 μm to 30 μm, and a third peak located in the range of 7 μm to 100 μm, with the first peak<second peak<third peak.

[0083] The modified resin composition of the present disclosure is not limited to a resin composition for use in molding a high-frequency device having an antenna, and may be a resin composition for use in other applications.

[0084] <High frequency devices> The high-frequency device of the present disclosure has an antenna and a cured product of the above-described resin composition.

[0085] The high-frequency device of the present disclosure is used, for example, when transmitting and receiving radio waves of 1 GHz or more, and preferably when transmitting and receiving radio waves of 3 GHz or more. The high-frequency device of the present disclosure may have a structure in which the cured product of the resin composition seals the antenna, or may have a structure in which the antenna is disposed on the cured product of the resin composition. EXAMPLES

[0086] The present invention will now be described in more detail with reference to examples, but the scope of the present invention is not limited to these examples.

[0087] <Preparation of Resin Composition> A resin composition was prepared by mixing the components shown below in the mixing ratios (unit: parts by mass) shown in Table 1. This resin composition was solid at room temperature and normal pressure. Also, blanks in Table 1 mean that the component was not mixed.

[0088] Epoxy resin 1: Triphenylmethane type epoxy resin, epoxy equivalent 167g / eq Epoxy resin 2: Biphenyl aralkyl type epoxy resin, epoxy equivalent 274g / eq Epoxy resin 3: Biphenyl type epoxy resin, epoxy equivalent 192g / eq Phenol hardener 1: Phenol aralkyl resin, hydroxyl equivalent 205g / eq Phenol hardener 2: Phenol novolac resin, hydroxyl equivalent 101g / eq Curing accelerator: 1,4-benzoquinone adduct of triphenylphosphine Coupling agent: N-phenyl-3-aminopropyltrimethoxysilane Release agent: Montan acid ester wax Colorant: Carbon black Additives: Side-chain modified epoxy / polyether modified silicone Inorganic filler 1: Spherical barium titanate with a volume average particle size (D50) of 6.5 μm (relative dielectric constant at 10 GHz: 46.3) Inorganic filler 2: Spherical silica particles with a volume average particle size (D50) of 40 μm (large particle size silica, relative dielectric constant at 10 GHz: 3.6) Inorganic filler 3: Spherical silica particles with a volume average particle size (D50) of 0.5 μm (small particle size silica, relative dielectric constant at 10 GHz: 3.6) Inorganic filler 4: Spherical alumina particles with a volume average particle size (D50) of 45 μm (large particle size alumina, relative dielectric constant at 10 GHz: 7.8) Inorganic filler 5: Spherical alumina particles with a volume average particle size (D50) of 0.7 μm (small particle size alumina, relative dielectric constant at 10 GHz: 7.8)

[0089] In addition, in the particle size distribution of the inorganic fillers measured using an image particle size distribution analyzer equipped with a Raman spectrometer, inorganic filler 1 has a peak in the range of 3 μm to 10 μm, inorganic fillers 2 and 4 have peaks larger than the peak of inorganic filler 1 and in the range of 10 μm to 60 μm, and inorganic fillers 3 and 5 have peaks in the range of 0.1 μm to 2 μm.

[0090] (Dielectric constant of inorganic filler) The relative dielectric constant of the inorganic filler was determined as follows. First, a resin composition of 100 parts by mass of epoxy resin (biphenyl aralkyl type epoxy resin, epoxy equivalent 274 g / eq), 74.8 parts by mass of phenol curing agent (phenol aralkyl resin, hydroxyl equivalent 205 g / eq), and 2 parts by mass of 1,4-benzoquinone adduct of triphenylphosphine, any one of inorganic fillers 1 to 5, and methyl ethyl ketone (MEK) were mixed, and the aforementioned resin composition was dissolved in MEK to prepare a varnish containing 75 mass% of the resin composition and inorganic filler in total. At this time, varnishes containing 10 volume %, 20 volume %, and 30 volume % of inorganic fillers 1 to 5 with respect to the solid content excluding the solvent were prepared. The obtained varnish was applied onto a substrate, and the substrate was dried at 100°C for 10 minutes, after which the resin film was peeled off from the substrate. The obtained resin film was molded by compression molding under conditions of a mold temperature of 175°C, molding pressure of 6.9MPa, and curing time of 600 seconds to obtain a cured product for measurement. The relative dielectric constant at 10GHz of each of the obtained cured products for measurement was measured, and a graph was created in which the content of the inorganic filler was plotted on the horizontal axis and the measured value of the relative dielectric constant was plotted on the vertical axis. From the obtained graph, a linear approximation was performed by the least squares method, and the relative dielectric constant when the content of the inorganic filler was 100% by volume was obtained by extrapolation, and this was taken as the "relative dielectric constant of the entire inorganic filler".

[0091] (Fluidity: Spiral flow) Using a spiral flow measurement mold conforming to EMMI-1-66, the resin composition was molded under the conditions of a mold temperature of 180°C, molding pressure of 6.9 MPa, and curing time of 90 seconds, and the flow distance (cm) was measured. The results are shown in Table 1.

[0092] (Gel Time) The gel time of the resin composition at 175°C was measured as follows. Specifically, 0.5 g of a sample of the resin composition was placed on a hot plate heated to 175°C, and the sample was uniformly spread in a circle of 2.0 cm to 2.5 cm at a rotation speed of 20 rpm to 25 rpm using a jig. The time from when the sample was placed on the hot plate until the sample lost its viscosity, became gelled, and peeled off from the hot plate was measured, and this was measured as the gel time (seconds). The results are shown in Table 1.

[0093] (Dielectric constant and dielectric tangent of the cured product) The resin composition was molded using a hand press under the conditions of a mold temperature of 175°C, molding pressure of 6.9MPa, and curing time of 600 seconds, and post-cured at 175°C for 6 hours. The cured product was cut into a plate-shaped test piece measuring 50 mm in length, 1 mm in width, and approximately 0.5 mm in thickness. The relative dielectric constant and dielectric loss tangent were measured at 25±3°C and 10 GHz using the test piece and a dielectric constant measuring device (Agilent, product name "Network Analyzer N5227A"). The results are shown in Table 1.

[0094] [Table 1]

[0095] As shown in Table 1, the resin compositions of Examples 1 to 15 were superior in fluidity to the resin composition of Comparative Example 1. Furthermore, it was possible to produce cured products having a relatively high dielectric constant using the resin compositions of Examples 1 to 15. For example, it is presumed that the resin compositions of Examples 1 to 15 can produce cured products having a higher dielectric constant than resin compositions using only silica particles or only alumina particles as an inorganic filler.

Claims

1. Epoxy resin, A hardener; A first inorganic filler containing elemental titanium; A second inorganic filler having a peak particle size of a particle size distribution different from the peak particle size of the particle size distribution of the first inorganic filler; Contains The content of the first inorganic filler is 60% by mass to 95% by mass based on the total amount of the first inorganic filler and the second inorganic filler, the second inorganic filler is silica or alumina; A resin composition for use in molding a high-frequency device having an antenna, wherein, with respect to the particle size distribution of the second inorganic filler, when the second inorganic filler is silica, there are two peaks derived from the second inorganic filler which is silica, and when the second inorganic filler is alumina, there are two peaks derived from the second inorganic filler which is alumina.

2. The resin composition according to claim 1 , wherein the first inorganic filler has a relative dielectric constant of 10 or more at 10 GHz.

3. The resin composition according to claim 1 or 2, wherein a particle size distribution of a combination of the first inorganic filler and the second inorganic filler has at least three peaks.

4. The second inorganic filler includes a third inorganic filler having a peak particle size of 0.1 μm to 5 μm in particle size distribution, and a fourth inorganic filler having a peak particle size of 7 μm to 100 μm in particle size distribution. The resin composition according to any one of claims 1 to 3.

5. The resin composition according to claim 4 , wherein the peak particle size of the particle size distribution of the first inorganic filler is larger than the peak particle size of the third inorganic filler and smaller than the peak particle size of the fourth inorganic filler.

6. The resin composition according to claim 4 or claim 5, wherein the mass ratio of the fourth inorganic filler to the third inorganic filler (fourth inorganic filler / third inorganic filler) is 0.1 to 5.

7. The resin composition according to any one of claims 1 to 6, wherein the first inorganic filler comprises at least one selected from the group consisting of barium titanate, calcium titanate, and strontium titanate.

8. Epoxy resin, A hardener; An inorganic filler; The particle size distribution of the inorganic filler has at least three peaks, and the inorganic filler includes a first inorganic filler containing titanium element and a second inorganic filler having a peak particle size of the particle size distribution different from the peak particle size of the particle size distribution of the first inorganic filler, The content of the first inorganic filler is 60% by mass to 95% by mass based on the total amount of the first inorganic filler and the second inorganic filler, the second inorganic filler is silica or alumina; Regarding the peaks of the particle size distribution of the inorganic filler, when the second inorganic filler is silica, there are two peaks derived from the second inorganic filler which is silica, and when the second inorganic filler is alumina, there are two peaks derived from the second inorganic filler which is alumina.

9. The particle size distribution of the inorganic filler has a first peak located in the range of 0.1 μm to 5 μm, a second peak located in the range of 0.5 μm to 30 μm, and a third peak located in the range of 7 μm to 100 μm, and the value of the first peak < the value of the second peak < the value of the third peak. The resin composition according to claim 8.

10. A high-frequency device comprising an antenna and a cured product of the resin composition according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Epoxy resin composition for semiconductor sealing and semiconductor device sealed therewith

    JP1990261856A

  • Epoxy resin composition for sealing semiconductor and semiconductor device using the same

    JP2007169655A

  • Highly dielectric epoxy resin composition and high-frequency device

    JP2010195997A

  • High-dielectric constant epoxy resin composition and semiconductor device

    JP2015036410A

  • Resin composition and resin-sealed type semiconductor device

    JP2018141052A